Mapping patterns of multiple deprivation using self-organising maps: An application to EU-SILC data for Ireland - Maurizio Pisati; Christopher T. Whelan; Mario Lucchini; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2009)
The development of conceptual frameworks for the analysis of social exclusion has somewhat out-stripped related methodological developments. This paper seeks to contribute to this process through the application of self-organising maps (SOMs) to the analysis of a detailed set of material deprivation indicators relating to the Irish case. The SOM approach allows us to offer a differentiated and interpretable picture of the structure of multiple deprivation in contemporary Ireland. Employing this approach, we identify 16 clusters characterised by distinct profiles across 42 deprivation indicators. Exploratory analyses demonstrate that position in the income distribution varies systematically by cluster membership. Moreover, in comparison with an analogous latent class approach, the SOM analysis offers considerable additional discriminatory power in relation to individuals' experience of their economic circumstances. The results suggest that the SOM approach could prove a valuable addition to a 'methodological platform' for analysing the shape and form of social exclusion.
Keywords: 330; Soziale Isolation; Einkommensverteilung; Sozialer Indikator; Irland